Cultural glocalisation in the era of video on demand: Content diversity in Netflix, HBO and Prime Video - Pedro, Josep (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Drawing on the concept of glocalisation and the practice of mapping, this article explores the diversity of content offered by three transnational subscription video-on-demand services: Netflix, HBO and Prime Video. Three categories linked to different dimensions of cultural diversity are proposed and applied: diversity of place; diversity of gender; and ethnic-racial diversity. In this way, the article identifies and classifies multiple works that represent and symbolise the presence and representation of dialogues between the global and the local, as well as of diverse identities in terms of origin, gender and/or “race” or ethnicity.